Cultural adaptation of cognitive–behavioural therapy. (November 2019) - Naeem, Farooq; Phiri, Peter; Rathod, Shanaya; Ayub, Muhammad
SUMMARY: The study of cultural factors in the application of psychotherapy across cultures – ethnopsychotherapy – is an emerging field. It has been argued that Western cultural values underpin cognitive–behavioural therapy (CBT) as they do other modern psychosocial interventions developed in the West. Therefore, attempts have been made to culturally adapt CBT for ethnic minority patients in the West and local populations outside the West. Some frameworks have been proposed based on therapists' individual experiences, but this article describes a framework that evolved from a series of qualitative studies to culturally adapt CBT and that was field tested in randomised controlled trials. We describe the process of adaptation, details of methods used and the areas that need to be focused on to adapt CBT to a given culture. Further research is required to move the field forward, but cultural adaptation alone cannot improve outcomes. Access to evidence-based psychosocial interventions, including CBT, needs to be improved for culturally adapted interventions to achieve their full potential. LEARNING OBJECTIVES: After reading this article you will be able to: recognise the link between cultural factors and the need to adapt psychosocial interventions identify the necessary steps to culturally adapt CBT understand the modifications required to deliver therapy to individuals from diverse cultural backgrounds. DECLARATION OF INTEREST: None.